1953
DOI: 10.1111/j.2042-7158.1953.tb13990.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Histamine and Antihistamines on Body Temperature

Abstract: THE body temperature decreasing effect of histamine in dogs and guinea-pigs was first described by Dale and Laidlawl. Similar results with regard to rats were observed by several authors ; Gyermek2 described that this effect increased as the environmental temperature decreased. In contrast, Leschke3 and Smith4 reported that histamine had no temperature lowering effect on rabbits. That antihistamines also exert a body temperature decreasing effect was reported by Ambrus, Ambrus, Jacob and H a m~s o n~~~~~~* , w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1955
1955
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…2: groups of four rats; x ---x, histamine reactions; A---A, 48/80 reaction. structure and in their reported effects (Packman, Rossi & Harrisson, 1953). The results are shown in Table 3.…”
Section: Histamine and Skin Reactionsmentioning
confidence: 89%
“…2: groups of four rats; x ---x, histamine reactions; A---A, 48/80 reaction. structure and in their reported effects (Packman, Rossi & Harrisson, 1953). The results are shown in Table 3.…”
Section: Histamine and Skin Reactionsmentioning
confidence: 89%
“…This possibility was supported by the evidence that various agents which lower body temperature, such as histamine, antihistamines, and pethidine (Packman, Rossi, and Harrisson, 1953; Dutta, 1948) also potentiate barbiturate anaesthesia (Winter, 1948;Ambrus, Ambrus, Leonard, Moser, and Harrisson, 1952;Kopera and Armitage, 1954).…”
mentioning
confidence: 52%
“…Among other substances found to lower rectal temperature and prolong pentobarbitone hypnosis were 5-hydroxytryptamine, for which potentiation of barbiturate has already been reported (Shore, Silver, and Brodie, 1955), adenosinetriphosphate, which is known to lower body temperature (Green and Stoner, 1950), and promethazine, for which both properties have been described (Courvoisier et al, 1953;Packman et al, 1953;Kopera and Armitage, 1954). Doses of these agents causing a similar decrease in temperature (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Chlorcyclizine was the antihistamine of choice since it combines potent antihistamine activity with minimal hypothermic activity (Packman et al, 1953). The experiments concerning antagonism by chlorcyclizine are of interest on several counts.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia is produced in several mammalian species by the injection of histamine into the peripheral tissues (Packman, Rossi & Harrisson, 1953). Studies using calorimetry have indicated that this action of histamine is mediated both by a decrease in heat production and by an increase in heat loss.…”
Section: Introductionmentioning
confidence: 99%